A Polyionic, Large‐Format Energy Storage Device Using an Aqueous Electrolyte and Thick‐Format Composite NaTi2(PO4)3/Activated Carbon Negative Electrodes. Issue 1 (5th November 2014) - Whitacre, J. F.; Shanbhag, S.; Mohamed, A.; Polonsky, A.; Carlisle, K.; Gulakowski, J.; Wu, W.; Smith, C.; Cooney, L.; Blackwood, D.; Dandrea, J. C.; Truchot, C.
Abstract A composite anode comprising blended NASICON‐structured NaTi2(PO4)3 and activated carbon has been implemented in an aqueous electrolyte electrochemical energy storage device. A simple solid‐state synthetic route based on low‐cost precursors was used to produce the NaTi2(PO4)3, and thick (>1 mm) freestanding electrodes were fabricated with a range of activated carbon mass fractions. Electrochemical analyses showed the efficacy and stability of this composite anode combination in a functional paradigm where both Na+ and Li+ cations can participate in the charge storage reactions. Use of this composite anode in concert with a λ‐MnO2‐based cathode results in an energy storage device that is low cost, robust, and of sufficient energy density to be implemented in stationary applications. Data from large‐format units that contain many cells in series indicate that string‐level self‐balancing occurs, an effect that can be relied on for making cycle‐stable high‐voltage strings of cells.